Pengaruh Pembelajaran Ekonomi Syari’ah Terhadap Minat Mahasiswa Menabung Di Bank Syariah (Studi Pada Mahasiswa Prodi Ekonomi Pembangunan Universitas Lampung - Syarifah Nurbaiti (Departement of Mathematics Education, 2024)
The Research intends to determine the influence of Syari’ah Economics Learning toward any interest yet of students in saving at Bank Syari’ah. This is implemented at the University of Lampung's Development Economics study program. Methods that used is a quantitative method. The analysis used by the author in This study is a simple regression analysis. Data sources of this study using primary data and secondary data. And the sampling technique in this study uses random sampling. These results show that learning Syari’ah Economics on student savings account at bank syari’ah, especially for students at the University of Lampung's Development Economics study program, it is giving a positive influence. The effect of syari’ah economics learning on students' means that greater the understanding of Bank Syari’ah in Syari’ah Economics learning, so the bigger it will be saving account’s students at Bank Syari’ah.